2019
DOI: 10.3390/resources8010039
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Relationships and Sustainability Performance in Organic Agriculture in the United Arab Emirates and Sicily (Italy)

Abstract: Climate change, recurrent economic and financial crises and food security issues are forcing society to look at the increasingly widespread use of “sustainable” production practices. These are often translated into innovations for businesses that are not always easily achievable other than through specific investments. This work sets out to assess the sustainability performance of organic farms, which represent a sustainable production model in terms of values, standards, practices and knowledge on the ground.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Low ratings in Atmosphere theme are related to the fact that farmers ignore the role of air as an ecosystem service. The absence of appropriate tools to measure actual pollution values generated by units’ activities [ 13 ] impedes the creation of awareness through mass media, extension and social networks, which would increase the acceptance of strategies to offset climate change [ 39 ]. Knowledge can influence air quality as integration of practices such as manure treatment, mixed-crop systems and feeding cattle with agricultural waste provide better atmosphere performance [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low ratings in Atmosphere theme are related to the fact that farmers ignore the role of air as an ecosystem service. The absence of appropriate tools to measure actual pollution values generated by units’ activities [ 13 ] impedes the creation of awareness through mass media, extension and social networks, which would increase the acceptance of strategies to offset climate change [ 39 ]. Knowledge can influence air quality as integration of practices such as manure treatment, mixed-crop systems and feeding cattle with agricultural waste provide better atmosphere performance [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SAFA framework has been previously used for several purposes, such as measuring the sustainability performance of organic farms in Italy and Saudi Arabia [ 13 ], or smallholding coffee farmers in Colombia [ 14 ]. Similarly, this tool was used to compare five types of agricultural systems, determining that all systems, excluding agribusiness, where similar to each other and had good performance in all sustainability dimensions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results correspond with the results of Melville (2010) and Gimenez et al (2015) who emphasize that ICT tools can enable organizational practices and processes that improve environmental and economic performance. We also found that it is worth to interpret environmental performance in a wider sense, and add input, outcome and strategic dimensions to process and output-oriented indicators (Schultze & Trommer, 2012;Butti et al, 2019;Gaviglio et al, 2017). Strategic indicators are quite important, environmental protection needs to be a strategic issue within a company (Benitez-Amado et al, 2015).…”
Section: Studies and Articlesmentioning
confidence: 83%
“…The sustainability-related analysis focuses on environmental sustainability based on the multidimensional environmental performance model suggested by Schultze and Trommer (2012). This model was chosen because the environmental performance of an organization is determined by different factors (Butti et al, 2019;Gaviglio et al, 2017), not exclusively by CO and other emissions which is widely used in the related literature (Lee & Brahmasrene, 2014;Ishida, 2015;Wang et al, 2015). The Schultze-Trommer-model distinguishes operational and strategic factors influencing environmental performance, and on operational level, it separates performance indicators related to the inputs, the processes, the outputs and the outcome.…”
Section: Studies and Articlesmentioning
confidence: 99%
“…The focus group (FG) methodology represents a participatory tool to achieve strategic orientation assessments, with guided group comparisons focusing on defined topics. The method is characterized by its dynamic nature and synergistic effects and leads to the definition of an information-rich system [69]. The approach makes it possible to deal with complex issues, using knowledge belonging to different scientific disciplines or specific stakeholder knowledge, to provide decision makers with a comprehensive and integrated bottom-up view [70].…”
Section: Participatory Planning Model and Selected Stakeholdersmentioning
confidence: 99%